SUSTAINABLE PRACTICE: THE REAL TRIPLE BOTTOM LINE - Aras, Guler; Crowther, David (EMERALD GROUP PUBLISHING LTD, 2013)
One of the children of Brundtland has been the concept of the triple bottom line - economic, environmental and social - as a means of planning for and measuring performance. This approach has largely been unquestioningly accepted. Despite this the agenda for socially responsible behaviour has evolved and developed. Now the concern is for the whole supply chain, which transcends the organisational boundary and throws a question over any idea of the triple bottom line. Corporate concern increasingly focuses upon two key issues, which are also of paramount importance to individuals: environmental degradation, particularly climate change, and human rights protection. In addition a lot of concern has been expressed as a result of revelations stemming from the economic and financial crisis, which have exposed significant failures in governance at corporate level and in markets and governments. Environmental degradation, human rights protection and governance operate at many levels from global to corporate. In many ways they parallel the idea of the triple bottom line but are not organisationally bounded. They represent issues of greater concern than merely corporate issues; they have an impact on the global and societal matters also. They are also totally connected to sustainable behaviour. In this chapter we therefore argue that this is the real triple bottom line, and discuss the implications.
Keywords: Sustainability; triple bottom line; human rights; governance; environment; stewardship; Business & Economics